1995
DOI: 10.3382/ps.0741591
|View full text |Cite
|
Sign up to set email alerts
|

Does Pulmonary Hypertension Syndrome (Ascites) Occur More Frequently in Broilers Medicated with Monensin?

Abstract: The performance of broilers reared in floor pens and given monensin in the feed at 121 ppm was compared with that of birds given no drug. Feed intake and BW gain of medicated birds was significantly lower than that of unmedicated birds from 0 to 22 d of age. Feed intake and feed conversion of medicated birds was significantly reduced, compared with unmedicated birds, from 22 to 53 and 0 to 60 d of age. Total mortality, and mortality due to leg abnormalities from 22 to 53 and 0 to 60 d, was significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…High concentrations of monensin have toxic effects upon the cardiovascular system of chickens (Hanrahan et al, 1981;Wagner et al, 1983) and Julian (1993) has suggested that monensin toxicity may result in mortality of up to 5% in broiler flocks caused by pulmonary hypertension (ascites). No differences in mortality due to ascites and no differences in right ventricle:total ventricular weight ratios or electrocardiogram values were observed in chickens reared in floor pens and given 121 mg/kg of monensin, indicating that pulmonary hypertension did not occur more frequently in birds given this drug (Chapman et al, 1995).…”
Section: Toxicitymentioning
confidence: 83%
“…High concentrations of monensin have toxic effects upon the cardiovascular system of chickens (Hanrahan et al, 1981;Wagner et al, 1983) and Julian (1993) has suggested that monensin toxicity may result in mortality of up to 5% in broiler flocks caused by pulmonary hypertension (ascites). No differences in mortality due to ascites and no differences in right ventricle:total ventricular weight ratios or electrocardiogram values were observed in chickens reared in floor pens and given 121 mg/kg of monensin, indicating that pulmonary hypertension did not occur more frequently in birds given this drug (Chapman et al, 1995).…”
Section: Toxicitymentioning
confidence: 83%
“…The extent to which chemical growth promotion affects these thyroid metabolic pathways, and hence ascites incidence, is poorly de® ned. One recent study showed no effect of treatment with monensin on the incidence of pulmonary hypertension syndrome (Chapman et al, 1995).…”
Section: The Role Of Infectious Agentsmentioning
confidence: 99%
“…No período de 1 a 21 dias de idade, não foi observado efeito significativo para CR, GP e CA entre os tratamentos nos três experimentos, à semelhança dos resultados de DAMRON (1994), porém contrariamente a CHAPMAN et al (1995), que observaram redução no CR e no GP em aves medicadas com 121 ppm de MON, aos 22 dias de idade.…”
Section: Resultsunclassified